Stakeholder engagement and the role of institutional dimensions - Jhunior, Ronaldo de Oliveira Santos (2023)
The current business environment is increasingly complex, with organizations realizing the importance of creating effective stakeholder engagement actions that yield positive outcomes and foster sustainable development for themselves and their stakeholders. Engaging with stakeholders can benefit organizations as it can help improve their reputation and overall success. Organizational actions can have far-reaching consequences that transcend national boundaries. To comprehend the impact organizations can have on a country or a global level, it\'s essential to understand how the institutional characteristics of different markets can either promote or hinder their contributions towards sustainable development. This doctoral dissertation addresses the current lack of understanding regarding companies\' stakeholder engagement considering varying institutional influences. Thus, by benefiting from the cross- fertilization of insights from stakeholder literature and institutional approaches, the central argument is that institutional dimensions, such as the State, Financial Markets, Social Capital, Human Capital, and Corporate Governance, play a role in stakeholder engagement behavior of companies under distinct institutional influences. The primary objective of this study is to analyze companies\' stakeholder engagement practices in light of their relations with the role of national institutions. In meeting this objective, it is possible to arrange the levels of stakeholder engagement considering the influence of institutional dimensions. The study method takes two steps: qualitative research through content analysis on stakeholder engagement practices in non- financial reports of sensitive publicly traded companies following the GRI Standards, and quantitative research on institutional dimensions categorized by the Varieties of Institutional Systems framework and the stakeholder engagement practices found in the previous step using multivariate quantile regression. The findings of this research establish communications with corroborating or contrasting with some prior theoretical endeavors. The results suggest that institutional dimensions significantly influence stakeholder engagement practices in emerging and middle-income economies, highlighting the Corporate Governance and Financial Markets dimensions. This investigation theoretically contributes to the literature by better understanding the relationship between stakeholder engagement and the institutional environment. It also generates social and managerial contributions by clarifying that companies must create stakeholder engagement strategies to succeed in developing countries, considering the institutional factors that influence stakeholder relationships. In sum, this knowledge can help enhance companies\' stakeholder engagement capabilities by considering the institutional systems in which they operate.